46, XX Ovotesticular disorder of sex development (true hermaphroditism) with seminoma: A case report. Issue 40 (2nd October 2020) - Li, Zixiang; Liu, Junjie; Peng, Yunpeng; Chen, Renfu; Ge, Peng; Wang, Junqi
Abstract: Rationale: Ovotesticular disorder of sex development (DSD), previously known as true hermaphroditism, is a disorder in which individuals have both testicular and ovarian tissues. Instances of tumors arising in the gonads of individuals with 46, XX ovotesticular DSD are uncommon. Patient concerns: We report a case of a 36-year-old phenotypical male with a chief complaint of an abdominal mass for 3 months. He reported normal erections and regular menses. Computerized tomography showed a large tumor measuring 15 × 10 cm in size, a uterus, and a cystic ovary. Diagnosis: 46, XX ovotesticular DSD with seminoma. Interventions: The patient was treated with neochemotherapy (etoposide and cisplatin), surgery, chemotherapy, and testosterone replacement. Outcomes: At the 13-month follow-up, the patient reported satisfactory erections, and no evidence of disease was found. Conclusion: Cases of 46, XX ovotesticular DSD with seminoma are uncommon. Our case reveals the importance of surgery combined with neochemotherapy, chemotherapy, and testosterone replacement in these patients to improve the prognosis.